Karyotypes of certain small mammals (Insectivora, Rodentia) from Macedonia - Zima, Jan (Scopolia, 1997)
Standard and banded karyotypes are reported for 14 species of insectivores androdents. Results are based on 99 specimens collected at 5 localities in western Macedonia: Sorex araneus, S. minutus, Neomys fodiens, Talpa stankovici, Dinaromys bogdanovi, Clethrionomys glareolus, Chionomys nivalis, Microtus arvalis, M. subterraneus, Nannospalax leucodon, Apodemus sylvaticus, A. flavicollis, A. mystacinus, and Dryomys nitedula.
Keywords: zoologija; zoology; mali sesalci; žužkojedi; glodalci; kariotipi; Makedonija; Republic of Macedonia